Aktivitas Ekstrak Kasar Enzim Kolagenase dari Organ Dalam Ikan Malong (Congresox talabon) pada pH Berbeda - Wikky Aditiya Putra; Anda rini Diharmi; Rahman Karnila (Jurnal Teknologi dan Industri Pertanian Indonesia, 2021)
Enzymes are biocatalysts that function as catalysts in biological functions. Collagenase enzymes have activities that can support product production. Enzyme activity for protein hydrolysis is influenced by several factors such as protein concentration, pH, temperature, substrate, inhibitor and activator. This study was aimed to determine the effect of differences in pH on the crude extract activity of the collagenase enzyme from the internal organs of malong fish. The study used a non-factorial completely randomized design, the treatments used were different pH (6.5, 7.5, and 8.5). This research consisted of several stages, namely sample preparation, extraction of internal organs to produce crude extract of the collagenase enzyme and test the activity of crude extract of the collagenase enzyme based on different pH. The analysis parameters was consisted of the proportion of fish yield, and the enzyme crude extract activity test at different pH. The results showed that malong fish has a proportion of meat 7,2 parts, bone 3,8, internal organs 1, skin 2,1. The yields of crude extract of collagenase enzyme pH 6.5, 7.5, and 8.5 were 60.83%, 64.09%, and 83.15%, respectively. The crude extract activity of collagenase enzyme from the internal organs of malong fish at pH 6.5, 7.5 and 8.5 was resulted in 0.293 U/ml, 0.5877 U/ml, and 0.7767 U/mL.  The highest collagenase enzyme crude extract activity was produced at pH 8.5.